Quiz (1 point)
- stack after popping a value from stack xs at index idx = reverse of (stack after popping a value from stack xs at index idx in traversed elements: [ ])
- stack after popping a value from stack [ x, xs ] at index idx in traversed elements: result = stack after popping a value from stack xs at index (idx - 1) in traversed elements: [ x, result ]
- 1 - 1 = 0
- stack after popping a value from stack [ x, xs ] at index 0 in traversed elements: result = result of dumping xs to result
- result of dumping [ y, [ ] ] to xs = [ y, xs ]
- reverse of [ x, [ y, [ ] ] ] = [ y, [ x, [ ] ] ]
if 1 - 1 = 0, then stack after popping a value from stack [ 12, [ 14, [ ] ] ] at index (1 - 1) in traversed elements: [ 10, [ ] ] = stack after popping a value from stack [ 12, [ 14, [ ] ] ] at index 0 in traversed elements: [ 10, [ ] ]
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
if stack after popping a value from stack [ 10, [ 12, [ 14, [ ] ] ] ] at index 1 in traversed elements: [ ] = [ 14, [ 10, [ ] ] ], then reverse of (stack after popping a value from stack [ 10, [ 12, [ 14, [ ] ] ] ] at index 1 in traversed elements: [ ]) = reverse of [ 14, [ 10, [ ] ] ]
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.